Mathematical Modeling and Optimization of the Monopoly Heating Market - Penkovskii, Andrey; Stennikov, Valery (International Journal of Energy Economics and Policy, 2020)
District heating plays a major role in many countries. Unlike markets of natural gas and electric power, district heating systems are local markets and in most cases, they organized as natural monopoly markets. This article examines the several variants for the formation of prices for household consumers on the heat energy market. For the conditions liberalized economy proposed a method of forming the price on the heat energy based on the search for market equilibrium of supply and demand on the monopoly heating market. For the conditions of the regulated heating market, the variants of forming the price of heat energy on the basis of average total and marginal costs are considered. To perform calculations, a mathematical model of the monopoly heating market is developed. It is based on the classical model of monopoly, basic models of the theory of hydraulic circuits and the theory of industrial markets and allows us to take into account the economic interests of the parties in fulfillment of physical and technical conditions and restrictions on the heat sources and heat networks. Practical calculations with help developed mathematical models were made for a real district heating system. Keywords: District Heating, Monopoly, Regulation, Mathematical Modeling, Optimization, Analysis. JEL Classifications: L43, L51, L95 DOI: https://doi.org/10.32479/ijeep.9284